EFEKTIVITAS KALENDER ISLAM GLOBAL DALAM HIFDZU AD-DIN PERSPEKTIF ILMU FALAK - Ardana, Alif Try; Maloko, M. Tahir (Universitas Islam Negeri Alauddin Makassar, 2025)
The usefulness of the Global Islamic Calendar from the Hifdzu Ad-din Perspective of Astronomy is examined in this thesis. The purpose of this study is to (1) determine the global Islamic calendar in Hifdzu ad-din from an astronomical standpoint. This study is quantitative in nature. The researcher employed the astronomical and shar'I approaches in this investigation. The primary data source used in this study was the Qur'an, books, journals, and other sources mentioned in the literature. The existence of organizations or nations that support their separate ijtihad serves as evidence that the research findings about the process of implementing the worldwide Islamic calendar are ineffective. One example is the State of Indonesia. The Indonesian state only imposes matla, only limited to territorial areas, not for all Muslims in the world. The implications for research from the application of the global Islamic calendar are divided into 2, namely negative and positive impacts. The positive impact of the implementation of the global Islamic calendar is that it can unite Muslims around the world in an integrated and integrated time. Meanwhile, the negative impact if the global Islamic calendar is not applied globally is that there is a classic problem related to the still strong and dominant understanding of local rukyat in each country, even groups in one country want to carry out rukyat in their respective places without caring about rukyat in other countries. In addition, the rejection of hisab also still colors the discourse of determining the beginning of the month, especially in the context of the global Islamic calendar. Furthermore, each country feels comfortable and there is no problem with its own methods and concepts, no matter how different there are with other countries that even the difference reaches a few days. Keywords: Global Islamic Calendar, Hifdzu Ad-Din, Astronomy